Breast Cancer: Follow-up Care - Martina Murphy; Karen Daily (EDIS, 2011)
The transition from active care to survivorship brings increased responsibility for women to monitor their own health and to do what they can to stay healthy. This 3-page fact sheet offers some information, guidance, and reassurance about what to expect in this next phase. Written by Martina Murphy and Karen Daily, and published by the UF Department of Family, Youth and Community Sciences, November 2011.